Tesis, Antitesis, dan Sintesis Terhadap Agama - Frederikus Fios (Humaniora, 2014)
From the beginning until now, religion has always been a paradoxical term. Religion has become an ambiguous term because it has both thesis and antithesis that are closely inherent. The thesis is that religion is positive strength striving for virtue, salvation, prosperity, happiness, and peace in the reality of human society globally and locally. On the other hand, religion also appears as negative force to be the antithesis of the religion itself. Problems rise on the religion lie not in the thesis but in the antithesis because thesis and antithesis are always accompanying the dynamics of religion in society reality. So that, it needs a "third way" as a tool to harmonize, align, and reconcile the contradiction. Research used qualitative method with critical hermeneutic approach intended to evaluate the antithesis of religion and show constructive side towards a better future. Based on the results and discussion, there is one thing called synthesis of religion. The synthesis area of religion should be an element that continues to be explored and optimized in order to create peace in the contemporary world and in the future. It takes an appreciation of positivistic religion so religion really becomes a force to liberate human beings from various negative phenomena which discolour the realm of religion.